Pengaruh Pakan Alternatif Berbasis Tanaman Lokal Terhadap Kinerja Ternak Ayam Kampung - Fatwamaty; Harun (CV. SINAR HOWUHOWU, 2025)
This study aims to examine the effect of alternative feed based on local plants on the performance of village chickens. The alternative feed used in this study consisted of local plants commonly found around the farming areas, such as moringa leaves, cassava leaves, and corn. The study involved village chickens divided into several treatment groups, with different compositions of alternative plant-based feed. The measured variables included body weight growth, feed intake, feed conversion ratio, and egg production. The results showed that the use of alternative feed based on local plants can improve the performance of village chickens, with better body weight and egg production compared to commercial feed. This indicates the potential of plant-based local feed as an economical and environmentally friendly alternative in village chicken farming.